Connection design in modular steel construction: A review. (October 2021) - Nadeem, Gohar; Safiee, Nor Azizi; Bakar, Nabilah Abu; Karim, Izian Abd; Nasir, Noor Azline Mohd
Abstract: Prefabricated modular steel construction can be an alternative to meet the growing demand for low-cost housing due to its rapid and economical construction techniques. The structural behaviour of modular steel connection is complex depending on the connection types and the degree of rigidity offered. In or only, or may connect both horizontally and vertically, depending to structurally behave as a single unit, it must be ensured that all the forces between modules are transferred effectively through intermodular connections. This paper presents a review of existing techniques used in the intermodular connections of the modular steel construction. The review presents a detailed discussion on the important characteristics of inter-modular connections such as geometric designs, the structural performances, and current design practices etc. The pros and cons of the existing connections are reviewed in terms of the structural performances through the previous available experimental and theoretical studies. The observations and discussion presented in this review can help to better understand and improve the connection behaviour in the modular structural systems.